Udział diaspory w wyborach krajowych: Przypadek Litwy, Polski i Węgier w ujęciu porównawczym - Dominik Héjj; Magdalena Lesińska; Dominik Wilczewski (University of Warsaw, Centre of Migration Research (CMR), 2021)
– The aim of the text is to present various models of participation of citizens residing abroad in national elections (external voting) and the organization of elections in the case of three countries: Poland, Lithuania and Hungary. There are large diasporas scattered around the world in these countries. However, they differ in the adopted legal regulations regarding the participation in state elections by citizens staying abroad. The text also provides an overview of the available data on the participation of citizens abroad in parliamentary and presidential elections in the country of origin, including the number of eligible voters and the number of votes cast abroad.
Keywords: 330; diaspora; emigration; external voting; Lithuania; Poland; Hungary